Quality, LMD formation system, pedagogical support - dahia, khaled (Journal of Social Sciences and Humanities, 2021)
This study aimed to examine whether there is a statistically significant relationship between organizational climate and organizational loyalty among employees in public administrations, To achieve the objectives of the study, a questionnaire was distributed to a random sample of 32 employees. The Organizational Loyalty Scale was used after adjusting it to fit the study sample. The results showed that there is a statistically significant relationship between the three dimensions of the organizational climate that are : the dimension of communication type, the dimension of participation in decision-making, and the motivation system dimension ; with organizational loyalty, as long as there is no correlation between organizational structuring and organizational loyalty; fact that Spearman's correlation coefficient between them is 0.09, and it is not statistically significant. there is a statistically significant relationship between variables, organizational climate and organizational loyalty, because the correlation coefficient is 0.98 which it shows a strong correlation at a significant level 0.01.